(untitled) (Research, Society and Development, 2020)
Teenage pregnancy has been considered a public health problem, and can generate complications, such as: gestational hypertensive syndromes, gestational diabetes mellitus, infant mortality, among others. From this assumption, the need to evaluate the dietary pattern of this population, through methods of food surveys, which should cover and understand different dimensions of the life of the pregnant woman. This study aims to analyze the food intake of pregnant adolescents attended in Basic Health Units, correlating with their nutritional status and socioeconomic factor. This is a quantitative, descriptive and cross- sectional study, which took place in the city of Cuité/PB, with 15 adolescent pregnant women assisted by Basic Health Units. A questionnaire was applied, which comprised the following data: General information, obstetric data, anthropometric evaluation, socioeconomic data and a Food Frequency Questionnaire. From this questionnaire, it was possible to observe the prevalence of low income, where most of the interviewees receive social benefits from the government, and most were overweight and obese. Regarding the food choice, the preference for processed and ultra-processed foods was perceived, and a low frequency of fresh and minimally processed foods. By relating these data to the socioeconomic profile, it was found that economic factors tend to negatively influence the Nutritional Status and food intake of young pregnant women. The results indicate the need to implement nutritional strategies for this population, focusing on the main difficulties mentioned above.